Analisa Keamanan Sistem Informasi RSUD Dr. Soetomo Dengan Framework COBIT - Natanael, Theodorus; Santoso, Leo Willyanto; Noertjahyana, Agustinus (Jurnal Infra, 2018)
RSUD Dr. Soetomo is one of the largest hospitals in Surabaya. Therefore, the complexity of information systems in RSUD Dr. Soetomo is very complex and covers a very wide area. With this complexity, it adds the risks possessed by RSUD Dr. information system. Soetomo. See the importance of data in information systems RSUD Dr. Soetomo, then the management of IT security needs to be considered.To implement the analysis of the Information System, it is necessary to have a good standard to be comparable with the standards of the Hospital. The Control Objective for Information and Related Technology (COBIT) framework has a goal to control IT related and is a well-recognized standard in international level.Problems faced by IT RSUD Dr. Soetomo is the absence of a letter of assignment, no written report, no risk mitigation, unfulfilled intent, purpose, and scope of work from IT Security. Companies can improve the security performance of information systems with guidelines that have good standards such as ISO, NIST, CNSSI.